Psychology of Debt in Rural South India - Arnaud Natal; Christophe Jalil Nordman (Institute of Labor Economics (IZA), 2024)
The relationship between personal debt and cognition has received limited attention, especially, in developing countries. This study focuses on India and examines the relationship between Big Five personality traits, cognitive skills (math, literacy, and Raven scores), and financial decision-making, specifically debt negotiation and debt management, while considering the weight of social identity (i.e., caste and gender). Using a panel dataset built from an original household survey conducted in 2016-17 and 2020-21 in rural Tamil Nadu and employing multivariate correlation probit analysis, we find the following. Firstly, conscientiousness is an advantage in the negotiation and management of debt, particularly for non-Dalit women, suggesting that, in a rural patriarchal context, women leverage personality traits to overcome the constraints of social identity. Secondly, emotional stability is a disadvantage in both debt negotiation and management. Thirdly, the role of cognition and in particular the Raven score is ambiguous (negative correlation with debt negotiation but positive correlation with debt management). Our results suggest that training programmes designed to improve conscientiousness, when integrated into broader macroeconomic policies, could help individuals secure better loan conditions and avoid repayment difficulties.
Keywords: D14; D91; G51; O1; 330; caste; Big Five; personality traits; cognitive skills; gender; social identity